E-GOVERNMENT SERVICE IN SAUDI ARABIA - Rahaj Nadrah, Yara Gambour, Rabea Kurdi, Renad Almansouri (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
With the world's rapid development, governments are introducing e-government to keep up with the progress. Public sectors therefore deal with a large number of people, the purpose of using this technology is to reduce costs, improve services, increase efficiency and save time. The government of Saudi Arabia has experienced several challenges in serving the citizen. This is because the Saudi Arabia government has served a very large population manually. This manual service delivery resulted in high government running costs and poor service delivery. The government has therefore introduced the E-government that is faster in terms of service delivery. Thus, this study discussed Saudi Arabia's efforts to implement the e-government and the challenges it faces, and its future plans for improving the 2030 vision. This study has discussed how Saudi Arabia's E-government framework has been employed and embraced. This report begins with an introduction and a brief background on E-government. The report then discusses the implementation of E-government in Saudi Arabia, the challenges faced and from then states the 2030 Saudi vision to improve e-government service. In addition, a comparison of Saudi Arabia's E-Government Development Index (EGDI) rating with the other Gulf countries was also presented.